Formalisation of the component specification - Vaidas Giedrimas; Audronė Lupeikienė (Lietuvos Matematikos Rinkinys)
This paper deals with the component specification and formalisation problems. It defines the notion of component model, gives the formalised concept of a component, compound component, and proposes to use hierarchical finite state machines as the formalism to specify component's life cycle.